2006
DOI: 10.1111/j.1365-2109.2006.01527.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent monitoring of temperature: an essential requirement for site selection in bivalve aquaculture in tropical-temperate transition zones

Abstract: Frequent monitoring of temperature (FMT) for over 1 year at two aquaculture sites in the western Baja California peninsula was analysed in terms of hourly, daily and monthly variability, and with this information, temperature‐change indices were calculated. These data were contrasted against a long‐term series from a global database (Extended Reconstruction of Sea Surface Temperature (ERSST)) to evaluate whether these could substitute for FMT. The compatibility of species requirements with the thermal conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 13 publications
0
22
0
4
Order By: Relevance
“…The highest densities and largest shell heights and the only commercial fishery of the species are found close to its northern distribution limit, where prevailing climate conditions are warm‐temperate (Morales‐Hernández & Cáceres‐Martínez ; Félix‐Pico, Arellano‐Martínez, Ponce‐Díaz & Massó‐Rojas ; Sicard et al . ). Therefore, overall growth performances of scallops cultured along the Baja California Peninsula tend to decrease with increasing in situ water temperatures (Freites et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The highest densities and largest shell heights and the only commercial fishery of the species are found close to its northern distribution limit, where prevailing climate conditions are warm‐temperate (Morales‐Hernández & Cáceres‐Martínez ; Félix‐Pico, Arellano‐Martínez, Ponce‐Díaz & Massó‐Rojas ; Sicard et al . ). Therefore, overall growth performances of scallops cultured along the Baja California Peninsula tend to decrease with increasing in situ water temperatures (Freites et al .…”
Section: Discussionmentioning
confidence: 97%
“…Water temperatures at the northern limit of scallop distribution on the Pacific side are much lower and much less variable than at southern bays and lagoons of the Baja California Peninsula (Sicard et al . ). The parents used from the Pacific population originated from Guerrero Negro lagoon in the north and were not cultured in their favourite native habitat even on the Pacific side, but at a more southerly location.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In general, Pacific oysters have a wide temperature tolerance as has been shown for adults (Sicard et al., ) and larvae (Rico‐Villa, Pouvreau, & Robert, ). However, empirical studies demonstrated that larvae are dependent on temperatures above 22°C to reach optimal growth and metamorphosis performance while temperatures as low as 17°C consistently inhibit ingestion and growth over the entire larval period, although they did not cause significant mortalities (Rico‐Villa et al., ).…”
Section: Discussionmentioning
confidence: 80%